Hypercortisolism and hyperandrogenism as manifestations of adrenal adenoma. Report on a Mexican girl and review of the literature - Paola de Baro-Álvarez; Lizbeth García-García; Olinka Reyes-Posada; Jorge Cortes-Sauza; Pedro A Sánchez-Márquez (Acta Pediátrica de México, 2014)
Background: Adrenal cortex tumors (ACT) are extremely rare in children and adolescents. Only 0.2% of all the new cases of cancer diagnosed in the United Stated and Europe are adrenal cortex tumors. The international incidence is not well defined, since it differs demographically. Due to the rarity of these tumors in children, little is known about their natural history.